2018
DOI: 10.1590/s1678-9946201860005
|View full text |Cite
|
Sign up to set email alerts
|

First case report of atypical disseminated cutaneous leishmaniasis in an opium abuser in Iran

Abstract: Leishmaniasis is a worldwide tropical infectious disease caused by different species of intracellular protozoa parasites of the genus Leishmania . Herein, we report a 78-year-old man with unusual diffuse cutaneous leishmaniasis (DCL) who had a history of opium abuse and chronic obstructive pulmonary disease (COPD). He had multiple papular, crusted and severely ulcerated lesions extended to his arm and chest. Direct smears and skin punch biopsy of the lesions were suggestive of leishmaniasis. Parasite DNA was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Despite the fact that all forms of CL are mainly caused by the same species, it is uncommon to see a relapse of MCL that manifests as DCL. 17 This might be evidence for increasing recent reports of DCL in the old world. 15 DCL could be with or without mucosal involvement and most of the time do not respond to treatment.…”
Section: Discussionmentioning
confidence: 74%
“…Despite the fact that all forms of CL are mainly caused by the same species, it is uncommon to see a relapse of MCL that manifests as DCL. 17 This might be evidence for increasing recent reports of DCL in the old world. 15 DCL could be with or without mucosal involvement and most of the time do not respond to treatment.…”
Section: Discussionmentioning
confidence: 74%
“…One important finding is the association of scarred skin lesions and also disseminated cutaneous lesions or coexistence of VL, particularly with L. major in immunosuppressed persons such as HIV‐positive persons, organ transplant recipients, and drug‐induced immunosuppression patients. Unfortunately, these extensive forms of CL owing to L. major and also other atypical forms of leishmaniasis are increasing in Iran . In the pathogenesis of MCL, high variability of Leishmania species and also Leishmania RNA viruses (LRVs) are involved.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports of diffuse CL from Iran. In 2018, Hashemi et al [9] reported a 78-yearold man with multiple papules, crusted and severely ulcerated cutaneous lesions that involved his arms and chest. This patient was known the case of chronic obstructive pulmo-…”
Section: Discussionmentioning
confidence: 99%